Critical Analysis of Piaget’s Theory and Educational Implications with Special Reference to Language Development - Alghofaili, Jawaher Fahad (American Journal of Education and Learning, 2021)
Jean Piaget’s contribution to understanding children’s first thought processes cannot be overstated. His theories on child cognitive development is based on their sensory development, egocentric representation, and language have been the prime focus in the paper. Nevertheless, his perspective and theories have been opposed and questioned by some scholars including Whorf (1956),Vygotsky (1962); Vygotsky (1978); Vygotsky (1987) and Baillargeon, Spelke, and Wasserman (1985). While this paper explores and expands on Piaget’s theories on the cognitive development of children, it also presents the perspectives of his other critics such as Repacholi and Gopnik (1997) and gives a broad overview of the research and theory of the cognitive development. Lastly, this paper offers strategies and suggestions in applying this knowledge in both the classroom and at home.